PENERAPAN METODE PEKERJAAN SOSIAL KELOMPOK DALAM BIMBINGAN KELOMPOK UNTUK MENANGANI PERILAKU BOLOS SEKOLAH PADA REMAJA DI KAWASAN JALAN TADUAN KOTA MEDAN - Sani Susanti; Michael Yudha Pratama; Yahya Rambe; Fredy Adrian Saragih; Herman Jaya Waruwu; Sabila Alvina; Hayunda Aura Sifa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
School truancy is one of the forms of juvenile delinquency that can negatively affect academic achievement, discipline, and adolescents' social development. This study aims to describe truancy behavior among adolescents, identify the factors contributing to such behavior, and analyze the implementation of the social group work method through group guidance in addressing truancy. The study employed a descriptive qualitative approach with data collected through observation, interviews, documentation, and the implementation of group guidance activities. The research was conducted in the Jalan Tanduan area, Medan City, involving adolescents aged 12–18 years who had a tendency to engage in truancy. The findings revealed that truancy behavior was influenced by several factors, including peer influence, low learning motivation, lack of parental supervision, and a social environment that was less supportive of education. The implementation of the social group work method through group guidance was carried out through the stages of formation, transition, activity, and termination. The intervention produced positive outcomes, including increased awareness among adolescents regarding the negative consequences of truancy, the importance of education, and the need for greater discipline in attending school. Therefore, the social group work method through group guidance can serve as an effective social intervention strategy for addressing truancy behavior among adolescents.